Prelimbic area to lateral hypothalamus circuit drives social aggression - Fuhai Bai; Lu Huang; Jiao Deng; Zonghong Long; Xianglin Hao; Penghui Chen; Guangyan Wu; Huizhong Wen; Qiangting Deng; Xiaohang Bao; Jing Huang; Ming Yang; et al. (iScience, 2023)
Summary: Controlling aggression is a vital skill in social species such as rodents and humans and has been associated with the medial prefrontal cortex (mPFC). In this study, we showed that during aggressive behavior, the activity of GABAergic neurons in the prelimbic area (PL) of the mPFC was significantly suppressed. Specific activation of GABAergic PL neurons significantly curbed male-to-male aggression and inhibited conditioned place preference (CPP) for aggression-paired contexts, whereas specific inhibition of GABAergic PL neurons brought about the opposite effect. Moreover, GABAergic projections from PL neurons to the lateral hypothalamus (LH) orexinergic neurons mediated aggressive behavior. Finally, directly modulated LH-orexinergic neurons influence aggressive behavior. These results suggest that GABAergic PL-orexinergic LH projection is an important control circuit for intermale aggressive behavior, both of which could be targets for curbing aggression.